Mapping of Rangeland Participatory Rangeland Management (PRM) Landscapes: Baringo & Wajir, Kenya - Sweta, L. (International Livestock Research Institute, 2022)
Management of rangelands involves the use of grazing land areas to ensure consistent livestock production while conserving the range resources sustainable utilization. Baringo and Wajir are dominated by pastoralism as the major livelihood. This creates need for participatory rangeland management (PRM) to promote productivity while reducing environmental degradation. The sustainable approach requires involvement of community in mapping existing resources, ecosystems and management mechanisms jointly agreed and adopted by the communities. Grazing areas require forage1 management to limit conflicts resulting from rangeland resource competition.